Mapoon Mission Station and the Privatization of Public Violence: - Jasper Ludewig (ABE Journal)
This paper considers the role of missionary architecture as an instrument of colonial governance. It focuses on the case of Mapoon, a German Moravian mission station established on the remote Cape York Peninsula in the colony of Queensland at the turn of the twentieth century. In its conception, the Mapoon mission would serve as a mechanism in the wider regulation of Queensland’s late-nineteenth-century colonial frontier, working to segregate the colony’s Aboriginal population from settler-colonial expansion. The architecture of the mission station formed the material basis of this project, redeploying aspects of a unique settlement model developed by Moravian Pietists since the eighteenth century. The paper argues that the history of Mapoon is one of transnational connection in which individual actors, organizational structures, and spheres of activity crossed porous imperial, colonial, and national borders. It examines this mobility—of ideas, expertise, and institutional projects—in order to rethink the conditions for telling a history of Australian architecture. It seeks to question the notional limits of these categories—of what can meaningfully be called “Australian” in this historical moment, and of what is deemed permissible as an example of historical “architecture”—in order to reveal that, even at its founding moment, Australia was already a global enterprise.